Cardiometabolic disease risk factors in pre- and postmenopausal women from four sub-Saharan African countries: A cross-sectional study. (June 2023) - Chikwati, Raylton P.; Mahyoodeen, Nasrin Goolam; Jaff, Nicole G.; Ramsay, Michele; Micklesfield, Lisa K.; Wade, Alisha N.; Agongo, Godfred; Asiki, Gershim; Choma, Solomon S.R.; Boua, Palwende R.; George, Jaya A.; Crowther, Nigel J.
Highlights: Risk factors for cardiometabolic disease (CMD) were found to be more common in East and South than West African women. CMD risk factors were found to have a higher prevalence in post- than in premenopausal women only in West Africa. CMD interventions in menopausal women in Africa must be tailored to each community. Abstract: Objective: To compare the risk factors for cardiometabolic disease between pre- and postmenopausal women from four sub-Saharan African countries. Study design: This cross-sectional study included 3609 women (1740 premenopausal and 1869 postmenopausal) from sites in Ghana (Navrongo), Burkina Faso (Nanoro), Kenya (Nairobi), and South Africa (Soweto and Dikgale). Demographic, anthropometric and cardiometabolic variables were compared between pre- and postmenopausal women, within and across sites using multivariable regression analyses. The sites represent populations at different stages of the health transition, with those in Ghana and Burkina Faso being rural, whilst those in Kenya and South Africa are more urbanised. Main outcome measures: Anthropometric and cardiometabolic variables. Results: The prevalence rates of risk factors for cardiometabolic disease were higher in South (Soweto and Dikgale) and East (Nairobi) Africa than in West Africa (Nanoro and Navrongo), irrespective of menopausal status. Regression models in combined West African populations demonstrated that postmenopausal women had a larger waist circumference (β = 1.28 (95 % CI: 0.58; 1.98) cm), log subcutaneous fat (β =0.15 (0.10; 0.19)), diastolic (β = 3.04 (1.47; 4.62) mm Hg) and log systolic (β = 0.04 (0.02; 0.06)) blood pressure, log carotid intima media thickness (β = 0.03 (0.01; 0.06)), low-density lipoprotein cholesterol (β = 0.14 (0.04; 0.23) mmol/L) and log triglyceride (β= 0.10 (0.04; 0.16)) levels than premenopausal women. No such differences were observed in the South and East African women. Conclusions: Menopause-related differences in risk factors for cardiometabolic disease were prominent in West but not East or South African study sites. These novel findings should inform cardiometabolic disease prevention strategies in midlife women specific to rural and urban and peri-urban locations in sub-Saharan Africa.